2016
DOI: 10.3855/jidc.6828
|View full text |Cite
|
Sign up to set email alerts
|

Association between blood group and susceptibility to malaria and its effects on platelets, TLC, and Hb

Abstract: Introduction: According to the World Health Organization, the estimated number of malaria cases in Pakistan is about 1.5 million. Hematological variables like platelets, total leukocyte count (TLC), and hemoglobin (Hb) need to be evaluated to diagnose malaria in suspects. This study aimed to investigate the association between blood group and susceptibility to malaria and effects on platelets, TLC, and Hb. Methodology: This was a case-control study with a sample size of 446, of which 224 were malarial cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…According to the current study, no significant association was found (p = 0.319) between the blood group and thrombocytopenia, and all ABO blood groups showed similar falls in platelet levels, suggesting that thrombocytopenia was not affected by the ABO blood groups. Studies from India, 59 and Pakistan 60 showed similar findings.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…According to the current study, no significant association was found (p = 0.319) between the blood group and thrombocytopenia, and all ABO blood groups showed similar falls in platelet levels, suggesting that thrombocytopenia was not affected by the ABO blood groups. Studies from India, 59 and Pakistan 60 showed similar findings.…”
Section: Discussionsupporting
confidence: 62%
“… 73 This could be a result of the sequestration of leukocytes, accelerated destruction, or decreased production. 74 The highest number of leukopenia was observed among blood group A (39.5%), followed by blood group O study participants (25.9%), in contrast with the studies conducted in India 59 and Pakistan 60 which were higher in B and AB blood groups, respectively. This discrepancy in results across different studies might be due to the methods they used for the determination of WBC counts and statistical tests that assume Gaussian distributions of data.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Blood group O susceptibility to anaemia may be attributable to the pathogenesis of malaria, gender or other unknown causes. Nevertheless, our study failed to establish the link between the ABO blood group among children with iron or noniron-containing MNP and anaemia, as postulated in other findings in India [ 68 ] and the case–control analysis in Pakistan [ 69 ].…”
Section: Discussioncontrasting
confidence: 61%
“…It intended to search the association between blood group distribution and susceptibility to malaria and effects on platelets, (total leukocyte count) TLC, and (hemoglobin) Hb. It concluded that no significant association exists between blood groups and susceptibility to malaria or developing anemia or thrombocytopenia [65]. Shakeel et al conducted a study at Nishter Hospital, Multan and Shaikh Zayd Hospital, Rahimyar Khan found that there was no significant difference between blood group frequency and Rh with chronic viral hepatitis [66].…”
Section: B) Malaria and Hepatitismentioning
confidence: 99%